2022
DOI: 10.1186/s13073-022-01048-4
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic single cell-based framework for digital twins to prioritize disease genes and drug targets

Abstract: Background Medical digital twins are computational disease models for drug discovery and treatment. Unresolved problems include how to organize and prioritize between disease-associated changes in digital twins, on cellulome- and genome-wide scales. We present a dynamic framework that can be used to model such changes and thereby prioritize upstream regulators (URs) for biomarker- and drug discovery. Methods We started with seasonal allergic rhinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In our disease model, we showed that neutralization of an UR which was predicted to target many different cell types over multiple developmental stages had a higher potential to prevent further disease-associated changes. Furthermore, the ranking was supported in samples from AD, UC, and CD [106], which confirms its relevance to other diseases as well. However, further studies will be needed to validate the potential of such high-ranked URs as therapeutic targets.…”
Section: Variable Changes Over the Developmental Stages Of Disease Co...supporting
confidence: 54%
See 2 more Smart Citations
“…In our disease model, we showed that neutralization of an UR which was predicted to target many different cell types over multiple developmental stages had a higher potential to prevent further disease-associated changes. Furthermore, the ranking was supported in samples from AD, UC, and CD [106], which confirms its relevance to other diseases as well. However, further studies will be needed to validate the potential of such high-ranked URs as therapeutic targets.…”
Section: Variable Changes Over the Developmental Stages Of Disease Co...supporting
confidence: 54%
“…We therefore reason that PDGF-BB should be a more effective target for treatment than IL-4. The importance of URs shared between multiple cell types and disease stages was further supported by a meta-analysis of non-lesional and lesional biopsies from patients with atopic dermatitis (AD), ulcerative colitis (UC), and Crohn's disease (CD) [106]. These analyses showed how known therapeutic targets and genes related to inflammation was found as top-predicted URs in MCDMs of both non-lesional and lesional samples, which were reasoned to represent different disease stages for each respective disease [106].…”
Section: Variable Changes Over the Developmental Stages Of Disease Co...mentioning
confidence: 98%
See 1 more Smart Citation
“…In an artificial pancreas model for patients with type 1 diabetes, mathematical models of human glucose metabolism and data algorithms that simulate insulin delivery are customized into the patient-specific DT model, which can continuously calculate insulin requirements and regulate blood insulin concentrations ( 37 , 38 ). Li et al presented a scalable framework for modeling and prioritizing disease genes and drug targets among dynamic changes in the DTs for seasonal allergic rhinitis ( 39 ).…”
Section: Current Applications Of the Digital Twin In Medicinementioning
confidence: 99%
“…The strategy for this type of study is illustrated in Figure 10. 26 Drug toxicities can also be predicted using interactomebased strategies. Just as disease modules connote a subnetwork of proteins and pathways that govern disease phenotype, drug toxicity modules provide the same kind of mechanistic insight into pathways that govern adverse drug effects.…”
Section: Network Medicine and Drug Target Identificationmentioning
confidence: 99%